Taṭwīr Ta`līm Mahārah al-Qirā‘ah Bi Ṭarīqah “Anṭiq Wa Mayyiz” `Alā Asās al-Madkhal as-Siyāqī Wa al-Madkhal al-Binā‘ī Bi MIN 9 Aceh Selatan - Ana Farhana; Hilmi Hilmi (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2023)
Based on the observation of the first-in-class fourth of the Government Islamic Primary School 9 South Aceh students are weak in pronouncing words and sentences in the text and students find it difficult to pronounce letters in Arabic words and have difficulty distinguishing the correct pronunciation. This also makes them feel weak in mastering the meaning of vocabulary and unable to understand the text. When the teacher distributes to groups and asks students to pronounce the words in the text and asks students to take turns reading they find it difficult to read. In the teaching and learning process, students cannot answer the teacher's questions about the text. With these problems, researchers want to develop learning reading skills with the